Occupational Job Ladders within and between Firms - Eliza Forsythe (Institute of Labor Economics (IZA), 2023)
I present four facts about occupational mobility: (1) most movements occur within firms, (2) downward moves are frequent, (3) wage growth reflects the direction and distance of mobility, and (4) relative occupational wages before mobility predict the direction of mobility, except for non-displaced movers between firms. I show these facts are consistent with models of vertical sorting. I show that non-displaced movements between firms obscure the positive selection of upward occupational movers, likely reflecting moves up a firm-wage job ladder. Displaced workers show similar predisplacement selection to internal movers, with pre-displacement occupational wage rank predicting the direction of occupational mobility.
Keywords: J31; J62; J63; M51; 330; job mobility; job ladders; displaced workers